Enhanced response to PD-L1 silencing by modulation of TME via balancing glucose metabolism and robust co-delivery of siRNA/Resveratrol with dual-responsive polyplexes. (April 2021) - Jia, Li; Gao, Yan; Zhou, Tong; Zhao, Xiu-Li; Hu, Hai-Yang; Chen, Da-Wei; Qiao, Ming-Xi
Abstract: Since cellular metabolism reprogramming is one of the crucial hallmarks of tumor, glucose metabolic pathways are emerging as an important target for modulating immunosuppressive tumor microenvironment (TME) in favor of anti-PD-L1 therapy. Aiming at boosting immune response by modulation immunosuppressive TME via balancing the glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) of tumor cells, we developed a dual-responsive mPEG-PLA-PHis-ss-PEI polyplexes (DRP/Res/siP) for robust co-delivery of PD-L1 siRNA and resveratrol (Res). Isothermal titration calorimetry confirmed the non-electrostatic interactions between PD-L1 siRNA and PHis block of the copolymer, which contributed to the efficient and synchronized release of siRNA with Res in response to the acidic and reductive environment by destabilizing the siRNA polyplexes. The extracellular acidification rate (ECAR) and the oxygen consumption rate (OCR) as well as some key enzymes involved in glycolysis and mitochondrial OXPHOS pathways were determined to quantify the glucose metabolism balance. Effective downregulation of glycolysis and upregulation of mitochondrial OXPHOS were observed in the tumor cells treated with DRP/Res/siP, leading to remarkably reduced lactate production and glucose consumption. In vivo anti-tumor results showed that upregulation of mitochondrial OXPHOS pathways not only significantly promoted CD8 + and CD4 + T cells infiltration, IFN-γ secretion but also significantly suppressed the Treg cells and MDSCs at the same glycolysis level, resulting in superior anti-tumor effect in combination with PD-L1 silencing. Our findings indicate that balancing glucose metabolic pathways of glycolysis and mitochondrial OXPHOS provides a more reliable immune boosting strategy to PD-L1 silencing than exclusive glycolysis inhibition.